(untitled) (Altre Modernità, 2017)
Pieter Vermeulen, Contemporary Literature and the End of the Novel: Creature, Affect, Form (New York, Palgrave Macmillan, 2015, 182 pp. ISBN 978113741452-6.) by Laura Colombino